sebuah ANALISIS STANDAR PENGELOLAAN PEMBIAYAAN DI SDN 128 PEKANBARU - Rahma Dinda; Syahrani Fitri Sibarani; Defvi Elena; Debi Sentia; Andre Irmanto; Sumianto . (CENDEKIA: JURNAL ILMIAH PENDIDIKAN, 2023)
This research was carried out because of the state of education financing management at SDN 128 Pekanbaru which was able to support the continuity of educational activities at the school. The purpose of this research was to find out the effectiveness of using school-owned funding sources, financial responsibility and transparency in school financial management, reducing errors in school financial management, and knowing the use of school finances for the quality of the learning process in class. The method used is a qualitative method with a single case study type that focuses on managing financing in education at SDN 128 Pekanbaru. Research data was collected using documentation and interviews. The results obtained from the research show that financially SDN 128 Pekanbaru does not experience difficulties in obtaining education funds, and the funds are also used for educational purposes. The principal shows good cooperation with the treasurer, so that the implementation of several school programs can be carried out properly.